Screening for Rice Blast Resistant Genes, Pi9, Pita, Pigm(t) and Pi54 in Landrace Rice Varieties of Northeastern Thailand - Krainart, Chinanat; Siangsai, Ratiros; Longya, Apinya; Sinumporn, Sitipun; Talumphai, Sucheela (Journal of Applied Research on Science and Technology (JARST), 2022)
Rice blast disease, caused by Magnaporthe oryzae, is one of the most frequent and significant impediments to sustainable rice production and the largest impediment to sustainable rice production. Effective control of this disease largely depends on identifying the resistant genes. In our study, 37 Thai landrace rice varieties (18 white-grain rice varieties and 13 colored-grain rice varieties) along with 6 improved white-grain rice varieties were screened for four rice blast resistant genes, Pi9, Pita, Pigm(t) and Pi54 by PCR technique using the gene-specific makers. The results showed that 20 rice varieties (54.0%) contained the rice blast resistant gene Pi9, 11 rice varieties (29.7%) contained the rice blast resistant gene Pita, 22 rice varieties (59.4%) contained the rice blast resistant gene Pigm(t) and 23 rice varieties (62.1%) contained the rice blast resistant gene Pi54. All 31 Thai landrace rice varieties carried at least one rice blast resistant gene(s). Four white-grain landrace rice varieties, four colored-grain landrace rice varieties and five improved rice carried the highest number of rice blast resistant genes at three genes, which can be used as the resistant donor in the rice breeding program. Two white-grain landrace rice varieties; Jao Dæng 2 and Mak Yom, contained one examined rice blast resistant genes. Two colored-grain landrace rice varieties; Nieow Dam (skn 3) and Kee Nok, contained all examined rice blast resistant genes. Five improved rice varieties contained three rice blast resistant genes. The information generated from this study is useful for parental selection in developing the new resistant rice varieties and breeding.